Pengaruh Media Pembelajaran Video Animasi Terhadap Hasil Belajar Siswa Pada Materi Bilangan Cacah Kelas II SD Negeri 01 Pemulutan Barat - Mahira, Jihan; Octaria, Dina; Septeiyawan, BZ. (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to determine the effect of animated video learning media on student learning outcomes in whole number material for class II SD Negeri 01 Pemulutan Barat. This research is a quantitative type using the True Experimental Design experimental research method with a Posttest-Only Control Design. The population of this study were all class II students at SD Negeri 01 Pemulutan Barat. The sample for this research was class II students. A and II. B with a total of 34 students. The sample selection technique used was census or total sampling. Data collection techniques in this research are observation, tests and documentation. Data analysis used the Independent Sample T-test. The results of this research show that the average posttest learning result score for the experimental class is 68.50 and the control class is 59.29. The results of the t-test calculation of learning outcomes obtained t_count = 2.687 > t_table = 2.037 with a significance level = 0.05. Based on the research results, it can be concluded that there is a significant influence of the use of animated video learning media on student learning outcomes in whole number material for class II SD Negeri 01 Pemulutan Barat.